Endovascular treatment for acute ischemic stroke in patients with tandem lesion in the anterior circulation: analysis from the METRICS study - Sanak, Daniel; Kocher, Martin; Zapletalova, Jana; Cihlar, Filip; Czerny, Daniel; Cernik, David; Duras, Petr; Fiksa, Jan; Husty, Jakub; Jurak, Lubomir; Kovar, Martin; Lacman, Jiri; et al. (Journal of neurointerventional surgery, 2023)
BACKGROUND: Acute ischemic stroke (AIS) due to anterior circulation tandem lesion (TL) remains a technical and clinical challenge for endovascular treatment (EVT). Conflicting results from observational studies and missing evidence from the randomized trials led us to report a recent real-world multicenter clinical experience and evaluate possible predictors of good outcome after EVT. METHODS: We analyzed all AIS patients with TL enrolled in the prospective national study METRICS (Mechanical Thrombectomy Quality Indicators Study in Czech Stroke Centers). A good 3-month clinical outcome was scored as 0-2 points in modified Rankin Scale (mRS), achieved recanalization using the Thrombolysis In Cerebral Infarction (TICI) scale and symptomatic intracerebral hemorrhage (sICH) according to the Safe Implementation of Thrombolysis in Stroke-Monitoring Study (SITS-MOST) criteria. RESULTS: Of 1178 patients enrolled in METRICS, 194 (19.2%) (59.8% males, mean age 68.7±11.5 years) were treated for TL. They did not differ in mRS 0-2 (48.7% vs 46.7%; p=0.616), mortality (17.3% vs 22.7%; p=0.103) and sICH (4.7% vs 5.1%; p=0.809) from those with single occlusion (SO). More TL patients with prior intravenous thrombolysis (IVT) reached TICI 3 (70.3% vs 50.8%; p=0.012) and mRS 0-2 (55.4% vs 34.4%; p=0.007) than those without IVT. No difference was found in the rate of sICH (6.2% vs 1.6%; p=0.276). Multivariate logistic regression analysis showed prior IVT as a predictor of mRS 0-2 after adjustment for potential confounders (OR 3.818, 95% CI 1.614 to 9.030, p=0.002). CONCLUSION: Patients with TL did not differ from those with SO in outcomes after EVT. TL patients with prior IVT had more complete recanalization and mRS 0-2 and IVT was found to be a predictor of good outcome after EVT.
Keywords: senioři; Thrombectomy; Stroke; senioři nad 80 let; Brain Ischemia; výsledek terapie; Middle Aged; Thrombolytic Therapy; Fibrinolytic Agents; mužské pohlaví; benchmarking; ischemická cévní mozková příhoda; Stent; Prospective Studies; cévní mozková příhoda; fibrinolytika; trombektomie; Aged, 80 and over; cerebrální krvácení; ženské pohlaví; Ischemic Stroke; Humans; prospektivní studie; endovaskulární výkony; lidé středního věku; Cerebral Hemorrhage; Endovascular Procedures; trombolytická terapie; ischemie mozku; Aged; Female; Benchmarking; Treatment Outcome; lidé; Male